Un modelo de Gestión de datos en una Unidad de Trasplante Hemopoyético - P. Balsalobre; R. Carrion; D. Serrano; I. Buño; A. Gómez-Pineda; S. Carrasco; J.L. Díez-Martín (Fundación para el Desarrollo de la Enfermería, 2005)
Resumen: La gestión de datos puede ser definida como una administración eficiente y sistemática de la información clínica con el objeto de dinamizar los procesos clínicos y la actividad investigadora. Presentamos el modelo de gestión de datos recientemente instaurado en nuestra unidad de Trasplante Progenitores Hemopoyéticos (UTPH). Metodología: En 2001 se llevó a cabo un proceso selectivo de un data manager. Con el objetivo de asegurar la coordinación entre los profesionales implicados en el trasplante y las instituciones que demandan información relacionada, los criterios seguidos fueron experiencia clínica, manejo de inglés y habilidades en el manejo de herramientas informáticas. Finalmente fue seleccionado un miembro del equipo de Enfermería. La gestión de información de la UTPH se basó en la configuración de un entorno de trabajo en red y en el uso de software específico (StemSoft®, ProMiSe®) y genérico. Resultados: El data manager asumió la coordinación de la agenda de trasplante con los médicos responsables de los pacientes candidatos (incluyendo la búsqueda de donantes) y otros servicios de soporte (Laboratorio molecular y HLA, radioterapeutas, banco de sangre y criopreservación). Para facilitar esta coordinación, se diseñó una herramienta específica (GesTHronica®). Se estableció una relación virtual estable con las instituciones relacionadas con el trasplante hemopoyéticos y las sociedades científicas nacionales e internacionales Se estableció un flujo regular de información con estas organizaciones con fines administrativos, de registro, clínicos y de investigación. Adicionalente, el data manager colaboró con el director del programa en la normalización y mantenimiento de los protocolos ubicados en la intranet de la UTPH. Conclusiones: Aunque la política de gestión de datos fue inicialmente prevista para mejorar el registro y la investigación de la actividad de trasplante, resultó util para incrementar la calidad asistencia. En este contexto, la relación con grupos científicos y la actividad investigadora fue marcadamente mejorada. Abstract: Data management can be defined as a systematic and efficient administration of clinical data in order to dynamize clinical processes and research activity. The aim of a data management policy is to offer a versatile response to clinical and research information demands, which is essential for quality improvement and achievement of accreditation standards within a bone marrow transplant setting. We would like to present an overview of the data management model recently implemented in our Stem Cell Transplant (SCT) Unit. Methods: A selection process for a data manager was performed in 2001. Clinical experience, English knowledge and ICT-informatics skills were required in order to assure an adequate coordination with both, the professionals involved in a SCT procedure and the institutions that demand SCT related information. We finally selected a professional among our nursing staff who met the selection criteria. The SCT information management was based on a net working environment (internet and intranet), using specific BMT software (StemSoft®, ProMiSe®) as well as general purpose software (word processors, spreadsheets, electronic databases and statistical packages). Results: Once a working environment based on the use of ofimatic and network tools was set up, the data manager assumed the coordination of the SCT schedule with doctors providing candidate patients for transplant (including the unrelated donor searching process) and other supporting services such as HLA typing and genetics labs, radiotherapy, blood bank and criopreservation unit. To facilitate this coordination, a specific electronic tool was designed on site (GesTHronica®). A virtual stable relationship with official SCT related institutions (National Transplant Organisation, regional health authorities, national marrow donor program...) and national and international scientific societies (Spanish Group for SCT, EBMT and IBMTR) was established. A regular information flow with these organisations was set up for administrative, registry, clinical and research purposes Additionally, the data manager helped SCT program director to normalise and keep accurate and updated the SCT SOPs, which were made available on line. Conclusions: Although data management policy was initially intended to improve registry and research SCT activity, it resulted useful to increase quality of clinical practice. Within this scenario, the relationship with scientific groups and research activity were positively improved. Centro de Trabajo: 31st Annual Meeting of the European Group for Blood and Marrow Transplantation, 21st Meeting of the EBMT Nurses Group, 4th Meeting of the EBMT Data Management Group Fecha del Trabajo: 01/03/2005 Palabra Clave: Gestión de datos, trasplante progenitores hemopoyéticos, investigación, Enfermería Key Words: Data management, Stem Cell Transplantation, Research, Nursing